2021
DOI: 10.1097/md.0000000000028121
|View full text |Cite
|
Sign up to set email alerts
|

The BISAP score, NLR, CRP, or BUN: Which marker best predicts the outcome of acute pancreatitis?

Abstract: Acute pancreatitis is a common disease, and the mortality rate can be high. Thus, a risk assessment should be performed early to optimize treatment. We compared simple prognostic markers with the bedside index for severity in acute pancreatitis (BISAP) scoring system to identify the best predictors of severity and mortality. This retrospective study stratified disease severity based on the revised Atlanta criteria. The accuracies of the markers for predicting severe AP (SAP) were assessed using rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Table 1 presents a summary of relevant studies. The 43 studies 24–65 included 14,116 AP patients, with mean/median age ranging widely (35–72 years) as the rate of male patients (34%–86%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents a summary of relevant studies. The 43 studies 24–65 included 14,116 AP patients, with mean/median age ranging widely (35–72 years) as the rate of male patients (34%–86%).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐four studies (79%) took place in Institutions in Asia, 24–28,30–35,37,39,41–52,54–56,58–62,65 7 in Europe, 36,38,40,53,57,63,64 2 in the USA 9,29 . Twenty‐one studies were prospective, 9,25,29,32–36,38,41,44,45,47,51–54,57,59,61,65 21 retrospective 24,26–28,30,31,37,39,40,42,46,48–50,55,56,58,60,62–64 and 1 cross‐sectional 43 . Three of the studies included both training and validation sets, 9,37,39 and one two cohorts of different age groups 50 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study 42 , the AUC for mortality based on the BISAP score was 0.88, and the sensitivity was 92% and the specificity was 76% when the cut-off value of the BISAP score was 3. In a study by Dancu et al 43 , the AUC for SAP based on the BISAP score was 0.77, and the sensitivity was 61% and the specificity was 88% when the cut-off value of the BISAP score was ≥2. Kim et al 44 showed that BISAP is more accurate in predicting the severity of acute pancreatitis than CTSI scores in a Korean population.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, exploring biomarkers for predicting mortality risk is in urgent demand to improve the outcome of AP. Currently, the main methods of predicting mortality risk in AP include bedside index for severity in acute pancreatitis scoring system and neutrophil-to-lymphocyte ratio at 48 h, whose measurement parameters are relatively complicated ( 31 , 32 ). To identify an accurate and simple approach for predicting mortality risk, differences in CDC42 expression between patients who succumbed to AP, SAP and MSAP and those who survived were evaluated.…”
Section: Discussionmentioning
confidence: 99%